KOMUNIKASI DAKWAH ISLAM UNTUK GENERASI Z - Suriati, Suriati; Suriyati, Suriyati; Muhlis, Muhlis; Musliadi, Musliadi; Imran, Muh. (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2026)
This study aims to analyze effective Islamic da'wah communication for Generation Z in the digital era. Generation Z, as a group born and raised in the midst of technological development, has distinct characteristics compared to previous generations, particularly in terms of communication patterns, media preferences, and how they receive information. This study used a qualitative approach with descriptive methods, using in-depth interviews, observation, and documentation studies as data collection techniques. The results indicate that effective da'wah communication for Generation Z must be interactive, creative, and relevant to everyday life. The use of social media such as short video platforms, podcasts, and visual content is the primary means of conveying da'wah messages. Furthermore, the use of simple, authentic language and a non-patronizing approach can increase the appeal and acceptance of da'wah messages. The conclusion of this study is that the success of da'wah to Generation Z is greatly influenced by the communicator's ability to adapt methods, media, and communication style to the characteristics of the audience. Therefore, innovation and adaptation in da'wah strategies are needed so that the Islamic message can be effectively received among Generation Z